2016
DOI: 10.20961/sainspet.v14i1.8776
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Pakan Suplemen Minyak Ikan Lemuru Dan Hidrolisat Darah Terproteksi Berdasarkan Kecernaan Bahan Kering Dan Kecernaan Bahan Organik Di Dalam Rumen Dan Pasca Rumen

Abstract: <pre><em>Increased of ruminants energy intake can be conducted by increasing the energy density of feed by using fat (oil). Protein intake can be enhanced by increasing of protected protein that escapes degradation by rumen microbes. The Aim of this research was to evaluate protected of feed supplement based on dry matter digestibility (KcBK), organic matter digestibility (KcBO) in vitro in the rumen and post-rumen. Protected feed supplement was produced from sardine fish oil and hydrolyzed blood ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Protozoa control the pH value of the rumen by utilizing easily fermentable carbohydrates for their daily needs, thereby slowing down the process of conversion of fermentable carbohydrates into lactic acid by rumen bacteria. Calcium soap supplementation in feed is quite effective in maintaining the acidity (pH) value in the rumen [9]. The addition of calcium soap in the ration is inert to the rumen so it does not change the rumen pH value [15].…”
Section: Ph Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Protozoa control the pH value of the rumen by utilizing easily fermentable carbohydrates for their daily needs, thereby slowing down the process of conversion of fermentable carbohydrates into lactic acid by rumen bacteria. Calcium soap supplementation in feed is quite effective in maintaining the acidity (pH) value in the rumen [9]. The addition of calcium soap in the ration is inert to the rumen so it does not change the rumen pH value [15].…”
Section: Ph Valuementioning
confidence: 99%
“…Calcium soap in a neutral rumen pH is stable and not easy to decompose, but the Ca and fatty acid bonds when passing through the abomasum with an acidic pH will be released and produce Ca ions and free fatty acids. This soap is also easy to mix with other feed ingredients [9]. One source of fat that can be used as calcium soap is BSF oil.…”
Section: Introductionmentioning
confidence: 99%
“…Utilisation of high oil levels in ruminant rations can impede the activity of rumen microbial agents. This is because liquid oil has physical properties that can coat feed particles, thus blocking rumen microbes from degrading the feed (Pramono et al, 2016). Therefore, to reduce this negative impact, oil can be administered in the form of protected oils, such as calcium soap (Pramono et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is because liquid oil has physical properties that can coat feed particles, thus blocking rumen microbes from degrading the feed (Pramono et al, 2016). Therefore, to reduce this negative impact, oil can be administered in the form of protected oils, such as calcium soap (Pramono et al 2013). Our hypothesized that using black solider y maggot oil in the diet of rams can improve male reproduction performance.…”
Section: Introductionmentioning
confidence: 99%
“…Oil addition to animal feed seems to be an effective method since oil has high energy density and low heat increment. Several studies reported the benefits of oil supplementation for reducing heat stress in animals [4,5].…”
Section: Introductionmentioning
confidence: 99%